Adaptations of students to on-line format in of higher learning - Dansheva , S.; Dytiuk , S.; Ihnatova , V.; Tesalovskaya , O. (New Collegium, 2021)
The article considers new requirements for higher education, the improvement of modern educational technologies such as training courses and distance learning technologies, and the study and identification of difficulties of students during the crisis caused by the pandemic. To date, a certain amount of knowledge important for formulating and solving the problem of adaptation of students during online education has been accumulated. Stating the active development of various aspects of the problem that we are investigating, we can conclude that the problem of adaptation of students to online learning using distance learning technologies and the difficulties that arise in this case have not yet become the subject of a special study. Questions about the effectiveness of distance or blended learning and the role of personal qualities of teachers and curators in the educational process are determined by primary importance of the problems of education and training at this stage of development of modern Ukraine. The article analyzes and identifies the socio-psychological state of the students and the problems they encounter during distance learning through questionnaires using Google Forms, and draws conclusions on how to solve these problems.